Severe acquired tracheomalacia caused by a chronic esophageal foreign body - Collin F. Mulcahy; Joseph C. Park; Eva I. Rubio; Allison L. Speer; Andrea Badillo; Maria Pena (Elsevier, 2019)
A 3-year-old otherwise healthy boy presented with new-onset progressive stridor that began 3 months prior. He was noted to have dyspnea on exertion, inspiratory stridor, and occasional regurgitation of undigested food. Direct laryngoscopy with bronchoscopy revealed tracheomalacia of the cervical trachea with marked compression extending down to 2 cm above the carina. Magnetic resonance imaging, computed tomography, and esophagram confirmed the presence of an esophageal foreign body with extensive inflammatory changes of the cervical and thoracic esophagus with mass effect causing compression on the trachea. Flexible esophagoscopy under sedation revealed a 2.9 cm × 2.5 cm hard plastic toy in the shape of rabbit ears, which was removed. The patient was extubated in the intensive care unit and was quickly advanced to a soft diet. He was asymptomatic at follow up 3 weeks after his procedure. Esophageal foreign bodies usually present with respiratory symptoms or feeding issues due to direct compression, and the presentation is typically acute. The finding of severe tracheomalacia has only been described in a few case reports. This is an unusual case of severe tracheomalacia secondary to a chronic esophageal foreign body.